Water Use Efficiency of Trickle and Sprinkle Irrigation on Chrysant Plants (Chrysantemum sp) - . Saprianto; Nora H. Pandjaitan (PERTETA, 1999)
Chrysant plants (Chrysantemum, sp.) as a horticulture vegetation has an estetical and economical value. Irrigation system which is used for Chrysant plants in PT Tecsuco Nusasemesta's green house are sprinkle and trickle irrigations. The water supply has to be equal with the water consumption of the plants in order to get higher water use eflciency. This research tries to calculate water use eflciency of trickle and sprinkler irrigation and its irrigation cost for chrysant plants. Water economical value is higher than before, so water consumption as one of production factor have to be planned in order to get proper benefit for every comodity. One of the methods to get the higher eflciency of water use is irrigation scheduling.